Values Perceived by Teens in Their Preferred Television Series Character Through the Hall-Tonna Document Analysis - Alonso, Oihane Korres; Albizuri, Iciar Elexpuru (International Dialogues on Education Journal, 2015)
This study was carried out on a sample group of 50 adolescents in their last year of Compulsory Education and aimed to determine the perceived values by subjects in their favorite television characters through the Hall-Tonna document analysis. The basic hypothesis for the study was that television conveys values and constitutes one of the forces for socialization at play during adolescence. The data was collected by means of a personal essay about their favorite television series character. Results show that the values most commonly perceived by adolescents are related to belonging, play/recreation and competence/confidence. Social-oriented values were also found. It is concluded that the measurement instrument used may constitute an adequate tool for decoding the values perceived by adolescents in their favorite television characters. Based on these results, some methodological proposals are presented to promote student values development from actual to desired values profiles and to use television as an educational resource.